2018
DOI: 10.1155/2018/8109621
|View full text |Cite|
|
Sign up to set email alerts
|

The Effects of Fermented Laminaria japonica on Short‐Term Working Memory and Physical Fitness in the Elderly

Abstract: Considering the neuroprotective and antioxidant potential of fermented Laminaria japonica A. (FST), the purpose of the present study is to establish whether FST may be considered a viable, efficacious supplement that can be administered in later life to offset neurodegenerative conditions associated with aging. Forty senior subjects participated in a randomized, double-blind, and placebo-controlled study. Two groups were formed, one FST group (n = 32, 72.35 ± 5.54 yrs) and one placebo (CON) (n = 28, 74.57 ± 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 79 publications
(94 reference statements)
0
43
0
Order By: Relevance
“…The administration of Gaba-enriched product fermented by kimchi-derived lactic acid bacteria also improved long-term memory loss recovery in the cognitive function-decreased mice and increased the proliferation of neuroendocrine PC-12 cells in vitro [24]. Moreover, the Gaba-enriched fermented Laminaria japonica (GFL) provided a protective effect against cognitive impairment associated with dementia in the elderly [25]. In addition, Reid and colleagues have shown that GFL could improve cognitive impairment and neuroplasticity in scopolamine- and ethanol-induced dementia model mice [26].…”
Section: Pharmaceutical Properties Of Gabamentioning
confidence: 99%
“…The administration of Gaba-enriched product fermented by kimchi-derived lactic acid bacteria also improved long-term memory loss recovery in the cognitive function-decreased mice and increased the proliferation of neuroendocrine PC-12 cells in vitro [24]. Moreover, the Gaba-enriched fermented Laminaria japonica (GFL) provided a protective effect against cognitive impairment associated with dementia in the elderly [25]. In addition, Reid and colleagues have shown that GFL could improve cognitive impairment and neuroplasticity in scopolamine- and ethanol-induced dementia model mice [26].…”
Section: Pharmaceutical Properties Of Gabamentioning
confidence: 99%
“…It has been reported that FST supplementation reduce obesity and improve stress management [29]. Furthermore, previous studies have shown that FST can protect against age-associated short-term memory loss and reduced physical functioning [30,31,32]. However, the effect of FST on bone has not previously been investigated and therefore we decided to investigate whether FST had any inhibitory effect on RANKL-stimulated osteoclast differentiation using RAW 264.7 mouse macrophage cells.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in most reports, no direct interaction but rather an indirect modulation of signaling was reported. For example, fermented Laminaria japonica, which contains fucoidan, increased serum BDNF levels in elderly subjects over a six week period [10]. Whether this effect translated to increased BDNF-signaling in those individuals was not reported.…”
Section: Discussionmentioning
confidence: 99%